Analisa Lithologi Lapisan Tanah Teluk Piyai (Kubu) - Panipahan Rokan Hilir Riau - Bambang Edison; Arie Syahruddin (Aptek, 2020)
Infrastructure development planning in the field of Civil Engineering must be able to accommodate the conditions of the new built environment, and must be known in detail. This can eliminate problems that will be interrelated in the future both in terms of planning and design, the final result must reflect the desires described. This research aims to conduct a geotechnical investigation to obtain detailed lithological information on soil structure in the Piyai Bay, Rokan Hilir Province Riau Methods of Implementation Research carried out includes two groups namely field testing and laboratory testing. Field testing was carried out with boring in order to get a sample to a depth of 30 meters. The results of the study of soil structure in the Piyai Bay (Kubu) - Panipahan - North Sumatra Boundary, Rokan Hilir Regency, Riau Province have a value of a relatively low base soil density based on N-SPT testing with lithology of peat to expansive soils, which have a large decrease, from field testing using core drill obtained soil lithology at a depth of 30 meters is fine silt sand, bright gray color, low plasticity to non-plastic, low water content, solid consistency until very dense . The result of monitoring graund water level (gwl) at the borehole point is 0.80 gwl.